1988
DOI: 10.1007/bf02555153
|View full text |Cite
|
Sign up to set email alerts
|

Increased3H-uridine levels in osteocytes following a single short period of dynamic bone loadingin vivo

Abstract: Both ulnas of skeletally mature roosters (Gallus domesticus) were deprived of functional load bearing by proximal and distal submetaphyseal osteotomies. Twenty-four hours later the animals were injected with 1.5 mCi of 3H-uridine and the ulna on one side was subjected to a single period of a cyclical load engendering physiological strain levels at 1 Hz for 6 min. Twenty-four hours after loading the animals were killed. Autoradiographic examination of comparable regions of cortex in sections from the bone's mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 12 publications
1
54
0
2
Order By: Relevance
“…Six hours after loading, radioactive osteocyte RNA was significantly increased in the loaded cores compared to unloaded cores. Pead, Suswillo, Skeny, and Lanyon (1988) showed that a single period of loading resulted in the transformation of quiescent lining cells into active osteoblasts within 5 days of the load stimulus.…”
Section: Mechanical Straw Homeostasismentioning
confidence: 99%
“…Six hours after loading, radioactive osteocyte RNA was significantly increased in the loaded cores compared to unloaded cores. Pead, Suswillo, Skeny, and Lanyon (1988) showed that a single period of loading resulted in the transformation of quiescent lining cells into active osteoblasts within 5 days of the load stimulus.…”
Section: Mechanical Straw Homeostasismentioning
confidence: 99%
“…intracellular calcium | cell process attachment | fluid flow activation | purinergic signaling A dynamic and complex structure such as bone has the ability to adapt and to adjust to changes in its functional environment. Emerging evidence suggests that osteocytes play an important role in regulating bone mechanoadaptation and in adjusting and maintaining bone mass (1)(2)(3)(4)(5)(6). Osteocytes, which account for ∼90% of the entire bone cell population, are viewed as the main mechanosensing cells that detect whole tissue mechanical loading due to their unique distribution throughout the mineralized matrix and to their connection to the neighboring osteocytes and osteoblasts via gap junctions (7).…”
mentioning
confidence: 99%
“…The authors declare no conflict of interest. 1 To whom correspondence may be addressed. E-mail: weinbaum@ccny.cuny.edu or mia.thi@einstein.yu.edu.…”
mentioning
confidence: 99%
“…What is not clear at present is the mechanism of response to loading, although recent evidence suggests a possible role for the osteocyte (Pead et al 1988). …”
Section: R E S P O N S E T O E X T E R N a L S T I M U L Imentioning
confidence: 99%
“…This remodelling process is also important in intramembranous (skull growth) and endochondral bone formation during bone development and growth. The osteocyte, which is an osteoblast embedded in the matrix, is probably responsible for sensing the changes in mechanical demand (Pead et al 1988). …”
mentioning
confidence: 99%